2012
DOI: 10.1523/jneurosci.6038-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Firing Correlates of Physiologically Distinct Cell Types of the Rat Dentate Gyrus

Abstract: The dentate gyrus (DG) occupies a key position in information flow through the hippocampus. Its principal cell, the granule cell, has spatially selective place fields. However, the behavioral correlates of cells located in the hilus of the rat dentate gyrus are unknown. We report here that cells below the granule layer show spatially selective firing that consists of multiple subfields. Other cells recorded from the DG had single place fields. Compared to cells with multiple fields, cells with single fields fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
181
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(203 citation statements)
references
References 54 publications
20
181
2
Order By: Relevance
“…Sparse DG activity was originally noted by O'Keefe and colleagues during their seminal work defining the in vivo firing properties of hippocampal neurons (O'Keefe and Nadel 1978) and very sparse activity is now viewed as a distinctive feature of the DG (Chawla et al 2005;Neunuebel and Knierim 2012). Over the subsequent three-and-half decades surprisingly few papers have been published on the natural firing patterns of DG GCs, indicative of the technical difficulties of recording in this area.…”
Section: The Mammalian Dentate Gyrusmentioning
confidence: 99%
See 3 more Smart Citations
“…Sparse DG activity was originally noted by O'Keefe and colleagues during their seminal work defining the in vivo firing properties of hippocampal neurons (O'Keefe and Nadel 1978) and very sparse activity is now viewed as a distinctive feature of the DG (Chawla et al 2005;Neunuebel and Knierim 2012). Over the subsequent three-and-half decades surprisingly few papers have been published on the natural firing patterns of DG GCs, indicative of the technical difficulties of recording in this area.…”
Section: The Mammalian Dentate Gyrusmentioning
confidence: 99%
“…However, Neunuebel and Knierim (2012) have recently suggested that previous studies may not have been recording from matGCs. By systematically tracking the position of their recording electrodes through the GCL, these authors report that matGCs in the outer GCL have single, small, discrete place fields, i.e., each matGC represents a very specific aspect of a given environment.…”
Section: Adult Hippocampal Neurogenesis and Its Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vivo The firing pattern of mature GCs in vivo is largely unclear (Neunuebel and Knierim, 2012). We therefore first determined the frequency of action potential initiation in rigorously identified mature GCs in vivo ( Figure 2; Table 1).…”
Section: Sparse Action Potential Generation In Hippocampal Gcsmentioning
confidence: 99%